Α-Cyperone of Cyperus rotundus is an effective candidate for reduction of inflammation by destabilization of microtubule fibers in brain. (24th December 2016) - Azimi, Azam; Ghaffari, Seyed Mahmood; Riazi, Gholam Hossein; Arab, Seyed Shahriar; Tavakol, Mohammad Mehdi; Pooyan, Shahriar
Abstract: Ethnopharmacological relevance: Cyperus rotundus L. (Cyperaceae), commonly known as purple nutsedge or nut grass is one of the most invasive and endemic weeds in tropical, subtropical and temperate regions. This plant has been extensively used in traditional medicine for anti-arthritic, antidiarrheal and antiplatelet properties as well as treatment for several CNS disorders such as epilepsy, depression and inflammatory disorders. Inflammation is evidently occurring in pathologically susceptible regions of the Alzheimer's disease (AD) brain as well as other disorders. Many cellular processes are responsible in chronic inflammation. Microtubule-based inflammatory cell chemotaxis is a well-recognized process that influences production of cytokines and phagocytosis. The effect of α-Cyperone, one of main ingredients of Cyperus rotundus on microtubule assembly and dynamics has not been examined and is the purpose of this investigation. Materials and methods: Microtubules and tubulin were extracted in order to explore their interaction with α-Cyperone by utilization of turbidimetric examinations, intrinsic fluorescence and circular dichroism spectroscopy (CD) studies. The molecular docking analysis was executed in order to facilitate a more detail and stronger evidence of this interaction. The BINding ANAlyzer (BINANA) algorithm was used to evaluate and further substantiate the binding site of α-Cyperone. Results: It was demonstrated that α-Cyperone had a pronounced influence on the tubulin structure, decreased polymerization rate and reduced concentration of polymerized tubulin in vitro. The CD deconvolution analysis concluded that significant conformational changes occurred, demonstrated by a drastic increase in content of β-strands upon binding of α-Cyperone. The fluorescence spectroscopy revealed that a static type of quenching mechanism is responsible for binding of α-Cyperone to tubulin. Upon characterization of various biophysical parameters, it was further deduced that ligand binding was spontaneous and a single site of binding was confirmed. Transmission electron microscopy revealed that upon binding of α-Cyperone to microtubule the number and complexity of fibers were noticeably decreased. The computational analysis of docking suggested that α-Cyperone binds preferably to β-tubulin at a distinct location with close proximity to the GTP binding and hydrolysis site. The ligand interaction with β-tubulin is mostly hydrophobic and occurs at amino acid residues that are exclusively on random coil. The BINANA 1.2.0 algorithm which counts and tallies close molecular interaction by performing defined set of simulations revealed that amino acid residues Arg 48 and Val 62 have registered the highest scores and are possibly crucial in ligand-protein interaction. Conclusion: α-Cyperone binds and interacts with tubulin and is capable of distinctly destabilizing microtubule polymerization. The effect of this interaction could result in reduction of inflammation which would be highly beneficial for treatment of inflammatory diseases such as AD. Graphical abstract: